Lower-dose corticosteroid therapy in severe immune thrombocytopenia during pregnancy: The comparable efficacy and lower incidence of maternal complications - Xu, Xue; Liang, Mei-Ying; Wang, Yi-Lin; Wang, Jian-Liu; Zhang, Xiao-Hui (Frontiers in Pharmacology, 2022)
Background: This study assessed clinical efficacy of oral prednisone at low-dose (LD) versus the previous high-dose (HD) study in patients with severe immune thrombocytopenia during pregnancy and its side effects in maternal and neonatal outcomes. Study Design: Pregnant patients with ITP were enrolled in the study (platelet count＜30×109/L) between January 2015 and 2019. Forty-three patients received LD oral prednisone (0.25-0.5mg/Kg) as the initial treatment and were compared retrospectively with the 31 patients in the HD (1mg/Kg) study. The primary clinical end point was response rate and the secondary end point was maternal hemorrhagic events, complications and neonatal outcomes. Results: 35% patients responded (15/43) to the LD cortico-therapy, including 4 with complete response which was no less than HD therapy (35.5%). The bleeding symptoms of 10(30%) patients were ameliorated after 14 days of LD prednisone treatment. Preeclampsia occurred in 3 cases (7% of total) of which the incidence was obviously lower than previous study at HD (18%). There were no stillbirth nor miscarriage occurred at LD group and neonatal outcomes had no significant differences between two studies. Conclusion: LD prednisone therapy for severe ITP patients during pregnancy had equal efficacy than HD treatment. Besides, the decrease in doseage significantly reduce the incidence of hypertension.